Oxygen isotopes and human residential mobility in central western Argentina - Gil, Adolfo Fabian (2014)
Stable oxygen isotopes (d18O) from human bone apatite from central western Argentina (30º–37ºS latitude) were analysed to understand changes in human residential mobility during the Late Holocene. This region contains evidence for the use of domesticated plants over the last 2000 years (Zea mays, Cucurbita sp. and Phaseolus sp., among others), and previous models of prehistoric occupation have suggested a distinct change in mobility and population movement associated with their incorporation. The importance of these domesticates also seems to have varied geographically, being greater in the northern part of the region and declining as one moves south toward the limit with Patagonia. Expectations about patterns of residential mobility have varied accordingly. To better evaluate these models, we analysed carbonate d18O from the bone apatite of 71 individuals with radiocarbon dates spanning the last 6000 years. Given the existing evidence, we expected to see temporal and geographic differences in their oxygen isotope values associated with changes in residential mobility and the incorporation of different sources of drinking water available within the region. These expectations were not met. Significant variations were seen across all samples compared, both temporal and geographic, with no discernible differences among them. The data suggest that populations throughout the area were all highly mobile, and that this did not change with the incorporation of domesticates.